Inflation Differentials among Czech Households - Pavel Hait; Petr Janský (Charles University in Prague, Institute of Economic Studies (IES), 2014)
Inflation rates have traditionally been measured by the annualized percentage change in the price level of a market basket of consumer goods and services purchased by households. The market basket represents the spending patterns of average household. However, households differ in their spending patterns and there are differences in the price changes of various goods and services. Therefore, different households experience different inflation rates. This paper finds that these differences have been significant in the Czech Republic during the period 1995-2010. Only around 60 % of households actually experienced an inflation rate that was similar to the national average. Furthermore, the higher the average inflation rate over time, the lower the percentage of households whose inflation rate was similar to that average. The main determiners of inflation were expenditures for housing and energy and, especially for low-income households and pensioners, expenditures on food and non-alcoholic drinks. In most years, pensioners and low-income households faced significantly higher inflation rates than the average rate for the whole population.
Keywords: D12; H22; I31; 330; households; inflation; inflation differentials; relative prices